Differences in Adolescent Self-Concept Based On Gender: A Comparative Study on Students in Yogyakarta - Muyana, Siti; Danni Rosada, Ulfa; Mujidin (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
In a society still influenced by gender stereotypes, male and female adolescents tend to develop different self-concepts. This study aims to examine differences in self-concept among university students based on gender. Using a quantitative approach with a comparative design, the research involved 990 participants selected through a probability sampling method. Data were collected using a self-concept scale. Normality testing revealed that the data were not normally distributed (p < 0.005), whereas the homogeneity test indicated homogeneous data (p > 0.05). The Mann-Whitney test revealed a significant difference in self-concept between male and female students (p<0.05). Specifically, male students scored higher on the expectation aspect (Mean = 33), while female students scored higher on the self-evaluation aspect (Mean = 36). These findings highlight the importance of implementing gender-sensitive counseling services to support and strengthen adolescent self-concept in a balanced and inclusive manner. Keywords: self-concept, expectations, knowledge, self-assessment, gender